A predective determinant of quality of life among homestay program participants in Malaysia - Ibrahim, Yahaya; Amin, Aziz; Mohd Salleh, Ahmad Munir (2013)
Tourism industry in Malaysia had become very crucial and important in the era of globalization in the 21st century. In Malaysia, tourism is the second largest contributor to the economy after the manufacturing sector. In 2008, the numbers of tourists recorded 22.05 million and tourism had contributed RM49.6 billion (USD13.4 billion) in revenue. Apart from that the total receipts of RM6.3 million had contributed by the homestay program through 68,416 domestic visitors and 23,117 foreign visitors. Therefore the main objective of this study is to identify the predictive determinant of quality of life, government role and attitude that influenced the general well-being amongst the homestay participant. A total of 306 samples was taken from the Homestay Program participants and the data was processed and analyzed using the Statistical Package for Social Science (SPSS). Among the analysis is a reliability test, descriptive and inferential analysis. The growth of the home stay program has provided huge opportunities for the human development. These include positive impact to the rural socioeconomic development, social capital development, as well as increase the quality of life among participants in the homestay program.